PERANCANGAN SISTEM INFORMASI MANAJEMEN POSYANDU BALITA BERBASIS WEB DIDESA MARSAWA MENGGUNAKAN LARAVEL - Uliyanti, Rinci; Maiyana, Efmi (Jurnal SUTASOMA (Science Teknologi Sosial Humaniora), 2025)
Posyandu in Marsawa Village has an important role in community health services, especially mothers and toddlers. However, the Posyandu data management process is still done manually, making it prone to recording errors, takes a long time, is difficult to access, and makes it difficult to present reports quickly and accurately. This research aims to design a web-based Posyandu Management Information System using the Laravel framework to improve the efficiency and accuracy of data management. The research used the Research and Development (R&D) approach of the 4D model (Define, Design, Develop, Disseminate) which consists of: (1) Define, to identify information needs and constraints in managing Posyandu data; (2) Design, to design a responsive and easy-to-use system and web interface; (3) Develop, to build a system using web technology and conduct functional testing; and (4) Disseminate, to socialize system results to related parties. The test results show that this system is able to facilitate the recording of data on mothers and toddlers, service schedules, and reports on Posyandu activities digitally and centrally. The implementation of this system is expected to improve the quality of Posyandu services in Marsawa Village effectively and sustainably.